Evaluating primary school teachers’ effectiveness in gender equality practices: a case study of the Beni Mellal-Khenifra region - Droussi, Ottmane; Hilali, Abdelkrim; Saghraoui, Zineb; Belkacem, Abdelhakim (Frontiers in Education, 2025)
IntroductionGender equality in education is crucial for achieving sustainable development and social justice. Despite efforts to promote gender equality in primary education, disparities persist, particularly in regions like Beni Mellal-Khenifra, Morocco. This research assesses the effectiveness of primary school teachers in promoting gender equality practices within this region.MethodsDrawing on quantitative data collected from 80 primary school teachers, the study assesses teachers’ knowledge, attitudes, and practices related to gender equality.ResultsFindings reveal strengths in teachers’ commitment to equal opportunities but also highlight areas for improvement, including planning gender-sensitive strategies and addressing gender inequalities effectively.DiscussionTargeted interventions and professional development programs are recommended to improve teachers’ effectiveness in promoting gender equality. Generally, this research contributes to advancing gender equality in education and underscores the vital role of primary school teachers in fostering inclusive and equitable learning environments. Limitations related to self-report bias and translation issues are acknowledged.